The Influence of PMA, PMDN and Labor Force on GDRB in DKI Jakarta Province - Prakoso, Radhityo Adhi; Purmini, Purmini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of FDI, PMDN and the number of labor force on economic growth in DKI Jakarta province. The data used are secondary data from the Central Statistics Agency in the 2018-2022 period in districts / cities in DKI Jakarta province. The dependent variable in this study is GRDP while the independent variables used in this study are PMA, PMDN and the number of labor force. The data analysis method applied is panel data regression analysis with a random effect model. The results showed that PMA, PMDN and the number of labor force had a positive and significant effect on GDP.